A heavy-coated titanium dioxide for coating and preparation method thereof

By adopting a multi-layered coating structure, the problems of insufficient amount of titanium dioxide coating, excessive viscosity and difficult washing in the prior art are solved, efficient light scattering and hiding power are achieved, and production costs are reduced .

CN116445010BActive Publication Date: 2025-02-11LOMON BILLIONS GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310427549.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-20
Publication Date
2025-02-11
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

In the application of existing heavy-coated titanium dioxide, the viscosity of the coating slurry increases, and the difficulty of washing increases, resulting in less application.

Method used

By adjusting the composition and structure of the envelope layer, the structure of the coating layer is adopted, the coating layer is composed of the first aluminum oxide and barium sulfate composite envelope layer, the coating layer is loosened, and the coating layer is adjusted. Improve the envelope amount and light scattering ability of titanium dioxide.

Benefits of technology

The titanium dioxide coating amount and light scattering ability are significantly improved, and its hiding power and application performance in coatings are enhanced, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004189091720000091
    Figure BDA0004189091720000091
Patent Text Reader

Abstract

The present invention discloses a heavy-coated titanium dioxide for coatings and a preparation method thereof, wherein the titanium dioxide comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from the inside to the outside, a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer. The titanium dioxide provided by the present application may have a large coating amount, and when used in a coating system, it may effectively block filler particles, increase the amount of filler, and significantly reduce production costs. At the same time, the light scattering ability of the titanium dioxide may be improved, thereby improving the dry hiding power of the titanium dioxide and improving the application performance of the titanium dioxide in coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pigment preparation, and particularly relates to a heavily coated titanium dioxide for coatings and a preparation method thereof. Background Art

[0002] Among various coatings, fluororesin coatings are relatively popular among consumers due to the large electronegativity of the fluorine element introduced and the carbon-fluorine bond energy. They occupy a large market share. According to statistics, they can account for 60-70% of the market share. To reduce the cost of latex paint, the most effective way is to reduce the amount of emulsion and increase the filler, that is, to develop high PVC latex paint.

[0003] In the high PVC latex paint formula, the presence of a large number of fillers will cause "crowding". In order to better exert the performance of titanium dioxide, it is necessary to maintain an appropriate spacing in the paint film, that is, uniform dispersion, to improve the light scattering efficiency. The heavy-coated titanium dioxide can effectively block the particles due to the thicker film layer. However, there are several problems with the use of heavy-coated titanium dioxide: 1. The titanium dioxide content will decrease due to the increase in the coating amount, thereby reducing the hiding power in the application system; 2. The coating amount is large, and a large amount of soluble salts (usually sodium sulfate and sodium chloride) are introduced, causing the viscosity of the coating slurry to increase or even make it impossible to continue coating; 3. The difficulty of water washing increases, and the water consumption increases. As a result, heavy-coated titanium dioxide products are less used at home and abroad.

[0004] At present, there is only one heavy-coating product in China, and there are several products abroad, but the performance is average. The present invention not only saves energy and reduces consumption in the process, but also has outstanding application performance. Summary of the invention

[0005] The purpose of the present invention is to provide a heavy-coated titanium dioxide for coating and a preparation method in order to solve the deficiencies of the prior art.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] A heavily coated titanium dioxide for coating comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from inside to outside, a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer.

[0008] Preferably, the total coating amount of the coating layer is not less than 10% of the mass of the titanium dioxide substrate.

[0009] Preferably, the coating amount of the loose silicon oxide coating layer is 8 to 10% of the mass of the titanium dioxide substrate in terms of silicon oxide;

[0010] The coating amount of the first aluminum oxide and barium sulfate composite coating layer is 2 to 3.5% of the mass of the titanium dioxide substrate;

[0011] The coating amount of the second aluminum oxide and barium sulfate composite coating layer is 1.5-3.0% of the mass of the titanium dioxide substrate.

[0012] Preferably, the first aluminum oxide and barium sulfate composite coating layer is formed by adding Ba(AlO2)2 and Al2(SO4)3 to the titanium dioxide-based material slurry and homogenizing them;

[0013] The second aluminum oxide and barium sulfate composite coating layer is formed by simultaneously adding Ba(AlO2)2 and Al2(SO4)3 and homogenizing them.

[0014] Preferably, the loose silicon oxide film layer is formed by the following steps:

[0015] First, the pH of the titanium dioxide-based material slurry is adjusted, and then a soluble alkaline silicon source is added, the soluble alkaline silicon source is added for 30 to 50 minutes, and the loose silicon oxide film layer is obtained after homogenization for 20 to 40 minutes; wherein the pH is adjusted to a slurry pH between 6.5 and 7.5 after the soluble alkaline silicon source is added;

[0016] The coating temperature of the loose silicon oxide film layer is 25-40°C.

[0017] Preferably, the pH is adjusted to 2-3, and the soluble alkaline silicon source is barium silicate.

[0018] The method for preparing the heavy-coated titanium dioxide for coating as described above comprises the following steps:

[0019] Take titanium dioxide-based material slurry, and coat it with a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer in sequence to obtain the heavily coated titanium dioxide for coating.

[0020] Preferably, the PS of the titanium dioxide-based material slurry is 0.36-0.38 μm, and PSD is less than 1.6.

[0021] Preferably, the preparation method further comprises the following steps:

[0022] S1. Take titanium dioxide-based material slurry and adjust the temperature to 25 to 40 ° C;

[0023] S2. The pH of the slurry is adjusted to 8 to 10, and then Ba(AlO2)2 and Al2(SO4)3 are added simultaneously, and the pH of the co-current is maintained at 8.5 to 9.5, and a first aluminum oxide and barium sulfate composite coating layer is formed after homogenization; the amount of Ba(AlO2)2 is 1.4 to 2.5% of the mass of the titanium dioxide substrate; the amount of Al2(SO4)3 is 0.6 to 1.2% of the mass of the titanium dioxide substrate;

[0024] S3. Adjust the pH of the slurry to 2 to 3, ensuring that the pH is between 6.5 and 7.5 after adding the soluble alkaline silicon source in step S4;

[0025] S4. Adding a soluble alkaline silicon source for 30 to 50 minutes, and then homogenizing for 20 to 40 minutes to form the loose silicon oxide coating layer; the amount of the soluble alkaline silicon source is 8 to 10% of the mass of the titanium dioxide substrate in terms of silicon oxide;

[0026] S5. Add Ba(AlO2)2 and Al2(SO4)3 at the same time, maintain the parallel flow pH at 6.5-7.5, and form a second alumina and barium sulfate composite coating layer after homogenization; the amount of Ba(AlO2)2 is 1.0-2.0% of the mass of the titanium dioxide substrate; the amount of Al2(SO4)3 is 0.5-1.0% of the mass of the titanium dioxide substrate.

[0027] Preferably, the pH adjuster in step S2 is Ba(AlO2)2, and the pH adjuster in step S3 is sulfuric acid.

[0028] The titanium dioxide provided in the present application can have a large coating amount, and when used in a coating system, it can effectively block filler particles, increase the amount of filler, and significantly reduce production costs. At the same time, it can also improve the light scattering ability of the titanium dioxide, thereby improving the dry hiding power of the titanium dioxide and improving the application performance of the titanium dioxide in coatings. DETAILED DESCRIPTION

[0029] The invention provides a heavily coated titanium dioxide for coating, comprising a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from the inside to the outside, a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer.

[0030] In conventional technology, a large amount of silicon oxide is used for coating, and there is a problem that the viscosity of the slurry is too high and the coating cannot be smoothly performed. However, the present application first performs a composite coating of aluminum oxide and barium sulfate on the inner side of the silicon oxide film layer. The composite coating layer of aluminum oxide and barium sulfate can be produced by co-precipitation of aluminum sulfate salt and barium sulfate salt, and no soluble salt is produced, which is conducive to the stability of the viscosity and dispersibility of the coating system. In addition, the low cohesion and fluidity of barium sulfate make the coating system more dispersible, and prepare to ensure that the deposition of loose silicon oxide in the next step does not cause excessive viscosity. Therefore, the film layer has extremely high dispersibility, and at the same time, the aluminum and barium elements of the coating can also improve the isoelectric point of the coating slurry, avoiding the problem of excessive viscosity of the coating slurry caused by a large amount of loose silicon absorbing water. Therefore, a large amount of loose silicon oxide coating can be performed subsequently, and the silicon oxide coating amount can reach up to 10%, thereby greatly increasing the total coating amount of titanium dioxide, having a thicker film layer, and effectively blocking the particles. Moreover, barium sulfate can also provide higher whiteness and hiding power. Compared with dense silicon coating, loose silicon oxide coating has micropores filled with air in the loose silicon oxide film layer, which can increase the refractive index difference, improve the light scattering ability of titanium dioxide, and then improve the dry hiding power of titanium dioxide, making it suitable for coating system. Finally, aluminum oxide and barium sulfate composite coating is performed on the outside of the loose silicon oxide film layer. While aluminum oxide improves the dispersibility of titanium dioxide, barium sulfate can further improve the gloss, fluidity and weather resistance of titanium dioxide. Moreover, as mentioned above, aluminum oxide and barium sulfate can be produced by coprecipitation without producing soluble salts, which improves the compatibility with latex paint system and formula applicability.

[0031] Therefore, the titanium dioxide provided by the present application can have a large coating amount, and when used in a coating system, it can effectively block filler particles, increase the amount of filler, and significantly reduce production costs. At the same time, it can also improve the light scattering ability of titanium dioxide, thereby improving the dry hiding power of titanium dioxide and improving the application performance of titanium dioxide in coatings.

[0032] Preferably, the total coating amount of the coating layer is not less than 10% of the mass of the titanium dioxide substrate.

[0033] Further preferably, the coating amount of the loose silicon oxide coating layer, calculated as silicon oxide, is 8 to 10% of the mass of the titanium dioxide substrate; the coating amount of the first aluminum oxide and barium sulfate composite coating layer is 2 to 3.5% of the mass of the titanium dioxide substrate (calculated as the total amount of aluminum oxide and barium sulfate); the coating amount of the second aluminum oxide and barium sulfate composite coating layer is 1.5 to 3.0% of the mass of the titanium dioxide substrate (calculated as the total amount of aluminum oxide and barium sulfate).

[0034] Preferably, the first alumina and barium sulfate composite coating layer is formed by simultaneously adding Ba(AlO2)2 and Al2(SO4)3 to the titanium dioxide-based material slurry and homogenizing them; Ba(AlO2)2 and Al2(SO4)3 are used as aluminum sources and barium sources, so that all the coating elements are precipitated in the form of a film layer, reducing the increased soluble salt ions in the filtrate. For titanium dioxide with a large coating amount, it helps to stabilize the viscosity and dispersibility of the coating system, and the water washing efficiency will be greatly improved.

[0035] Preferably, the second aluminum oxide and barium sulfate composite coating layer is formed by simultaneously adding Ba(AlO2)2 and Al2(SO4)3 and homogenizing them.

[0036] Preferably, the loose silicon oxide film layer is formed by the following steps:

[0037] First, adjust the pH of the titanium dioxide-based material slurry, then add a soluble alkaline silicon source, the soluble alkaline silicon source is added for 30 to 50 minutes, and a loose silicon oxide film is obtained after homogenization for 20 to 40 minutes; the pH is adjusted to a slurry pH between 6.5 and 7.5 after the soluble alkaline silicon source is added. The main factors affecting the density of the film are deposition pH, deposition temperature and deposition time. The conditions for the formation of dense silicon are generally alkaline environment, high temperature of about 90°C, and a long deposition time (3% sodium silicate must be deposited for at least 120 to 150 minutes). The present application can obtain a loose silicon oxide film by quickly adding a soluble alkaline silicon source and quickly homogenizing under low pH conditions and at a relatively low temperature (25 to 40°C).

[0038] More preferably, the pH is adjusted to 2-3, and the soluble alkaline silicon source is barium silicate.

[0039] The soluble alkaline silicon source used in the coating process of the loose silicon oxide film layer is barium silicate, and the first aluminum oxide and barium sulfate composite coating layer and the second aluminum oxide and barium sulfate composite coating layer use Ba(AlO2)2 and Al2(SO4)3 as aluminum source and barium source. There is co-precipitation in the coating of each film layer, and no soluble salt is produced, which is helpful to stabilize the viscosity and dispersibility of the coating system and improve the water washing efficiency. In addition, co-precipitation has the advantages of "the formed nano-film layer is uniform, the particles are small and the specific surface area is large, the light reflection is more, and the covering power is higher."

[0040] The present application also provides a method for preparing the heavy-coated titanium dioxide for coating as described above, comprising the following steps:

[0041] Take titanium dioxide-based material slurry, and coat it with a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer in sequence to obtain heavily coated titanium dioxide for coating.

[0042] Preferably, the titanium dioxide-based material slurry is a chloride-based titanium dioxide slurry with good performance, with a PS of 0.36-0.38 μm and a PSD of <1.6. The particle size of the coating-based material slurry is higher than normal, which can improve the sand milling efficiency, reduce the sand milling energy consumption, and thus reduce the production cost of titanium dioxide. Moreover, particles with large particle sizes have small specific surface areas, and the molecular attraction and electrostatic attraction between the particles are relatively small, so they have good dispersibility in the slurry, which is conducive to the heavy coating of titanium dioxide.

[0043] Preferably, the preparation method further comprises the following steps:

[0044] S1. Take titanium dioxide-based material slurry, adjust the temperature to 25-40°C; start stirring;

[0045] S2. The pH of the slurry is adjusted to 8.5-9.5 for 5-15 minutes, and then homogenized for 5-15 minutes; then Ba(AlO2)2 and Al2(SO4)3 are added simultaneously, and the pH of the co-current is maintained at 8.5-9.5, and the co-current addition time is 15-25 minutes. After homogenization for 3-10 minutes, a first aluminum oxide and barium sulfate composite coating layer is formed; the amount of Ba(AlO2)2 is 1.4-2.5% of the mass of the titanium dioxide substrate; Al2(SO 4) The dosage of 3 is 0.6-1.2% of the mass of the titanium dioxide substrate; the purpose of first adjusting the slurry pH to alkaline (8.5-9.5) is to create an alkaline environment so that the crystals of Ba(AlO2)2 and Al2(SO4)3 deposited under alkaline conditions have better dispersibility; S3. Adjust the slurry pH to 2-3, the adjustment time is 15-25min, and then homogenize for 5-15min to ensure that the pH is between 6.5 and 7.5 after adding the soluble alkaline silicon source in step S4;

[0046] S4. Adding a soluble alkaline silicon source for 30 to 50 minutes, and then homogenizing for 20 to 40 minutes to form the loose silicon oxide coating layer; the amount of the soluble alkaline silicon source is 8 to 10% of the mass of the titanium dioxide substrate in terms of silicon oxide;

[0047] S5. Add Ba(AlO2)2 and Al2(SO4)3 at the same time, maintain the co-flow pH at 6.5-7.5, the co-flow time is 20-40 minutes, and form a second composite coating layer of aluminum oxide and barium sulfate after homogenization for 100-140 minutes; the amount of Ba(AlO2)2 is 1.0-2.0% of the mass of the titanium dioxide substrate; the amount of Al2(SO4)3 is 0.5-1.0% of the mass of the titanium dioxide substrate; since the pH after the previous reaction is 6.5-7.5, the pH of Ba(AlO2)2 and Al2(SO4)3 in this step is maintained at 6.5-7.5, and no pH regulator is required to adjust, thereby reducing the introduction of salt. At the same time, barium sulfate and aluminum oxide can also co-precipitate under this pH condition to form a second composite coating layer of aluminum oxide and barium sulfate; in addition, the neutral pH condition is also suitable for the use of downstream products;

[0048] S6. The above slurry is washed with water, flashed and steamed to obtain a titanium dioxide finished product.

[0049] The coating of the present application is carried out at low temperature or even room temperature, thereby reducing the energy consumption of electric heating or steam heating.

[0050] Ba(AlO2)2 and Al2(SO4)3 are added in the form of solutions, and the concentration of the solutions is 80-200 g / L. The soluble alkaline silicon source is added in the form of solutions, and the concentration of the solutions is 80-120 g / L in terms of silicon oxide.

[0051] Preferably, in order to reduce the introduction of salt ions, the pH adjuster in step S2 is Ba(AlO2)2, and the pH adjuster in step S3 is sulfuric acid.

[0052] The processes not limited in the present invention, such as water washing, flash evaporation, steam powder, etc., are all carried out in conventional ways in the art.

[0053] Example 1

[0054] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 300g / L, PS=0.367μm, PSD=1.582, stirring is turned on, and the temperature is raised to 30°C; within 10 minutes, the pH is adjusted to 8.5 with Ba(AlO2)2 solution and homogenized for 5 minutes; within 20 minutes, 1.4% Ba(AlO2)2 solution and 0.6% Al2(SO4)3 solution are added to the slurry at the same time, and the slurry is homogenized for 5 minutes; within 20 minutes, H2SO4 is added to the slurry to adjust the pH to 2.1 and homogenized for 10 minutes; within 50 minutes, 10% (in terms of silicon oxide) BaSiO3 solution is added, the pH is 6.6, and the slurry is homogenized for 30 minutes; 1.8% Ba(AlO2)2 solution and 0.8% Al2SO4 solution are added at the same time, the addition time is 30 minutes, and the slurry is homogenized for 120 minutes; the product is obtained by water washing, flash evaporation and steam powder.

[0055] Example 2

[0056] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 350g / L, PS=0.373μm, PSD=1.591, stirring is turned on, and the temperature is raised to 40°C; within 10 minutes, the pH is adjusted to 9 with Ba(AlO2)2 solution, and homogenized for 5 minutes; within 20 minutes, 2% Ba(AlO2)2 solution and 0.9% Al2(SO4)3 solution are added to the slurry at the same time, and homogenized for 5 minutes; within 20 minutes, H2SO4 is added to the slurry to adjust the pH to 2.7, and homogenized for 10 minutes; within 50 minutes, 9% (in terms of silicon oxide) BaSiO3 solution is added, the pH is 6.7, and homogenized for 30 minutes; 1.2% Ba(AlO2)2 solution and 0.54% Al2SO4 solution are added at the same time, the addition time is 30 minutes, and the homogenization is 120 minutes; the product is obtained by water washing, flash evaporation, and steam powder.

[0057] Example 3

[0058] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 300g / L, PS=0.371μm, PSD=1.585, stirring is turned on, and the temperature is raised to 35°C; within 10 minutes, the pH is adjusted to 9.5 with Ba(AlO2)2 solution and homogenized for 5 minutes; within 20 minutes, 2.4% Ba(AlO2)2 solution and 1.1% Al2(SO4)3 solution are added to the slurry at the same time, and the slurry is homogenized for 5 minutes; within 20 minutes, H2SO4 is added to the slurry to adjust the pH to 3.0 and homogenized for 10 minutes; within 50 minutes, 8% (in terms of silicon oxide) BaSiO3 solution is added, the pH is 7.0, and the slurry is homogenized for 30 minutes; 2% Ba(AlO2)2 solution and 0.9% Al2SO4 solution are added at the same time, the addition time is 30 minutes, and the slurry is homogenized for 120 minutes; the product is obtained by water washing, flash evaporation and steam powder.

[0059] Example 4

[0060] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 300g / L, PS=0.365μm, PSD=1.569, stirring is turned on, and the temperature is maintained at 25°C; within 10 minutes, the pH is adjusted to 9 with Ba(AlO2)2 solution and homogenized for 5 minutes; within 20 minutes, 2% Ba(AlO2)2 solution and 0.9% Al2(SO4)3 solution are added to the slurry at the same time, and the slurry is homogenized for 5 minutes; within 20 minutes, H2SO4 is added to the slurry to adjust the pH to 2.5 and homogenized for 10 minutes; within 50 minutes, 9% (in terms of silicon oxide) BaSiO3 solution is added, the pH is 6.5, and the slurry is homogenized for 30 minutes; 2% Ba(AlO2)2 solution and 0.9% Al2SO4 solution are added at the same time, the addition time is 30 minutes, and the slurry is homogenized for 120 minutes; the product is obtained by water washing, flash evaporation and steam powder.

[0061] Comparative Example 1 (without first aluminum oxide and barium sulfate composite coating)

[0062] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 300g / L, PS=0.367μm, PSD=1.582, stirring is turned on, and the temperature is raised to 30°C; H2SO4 is added to the slurry within 20 minutes to adjust the pH to 2.5, and homogenize for 10 minutes; 10% BaSiO3 solution is added within 50 minutes, and homogenize for 30 minutes; 3.2% Ba(AlO2)2 solution and 1.4% Al2SO4 solution are added at the same time, the addition time is 30 minutes, and the homogenization is 120 minutes; the product is obtained by washing, flash evaporation, and steam powder.

[0063] Comparative Example 2 (barium sulfate coating not used)

[0064] After the uncoated chloride titanium dioxide is crushed, wet-milled, sand-milled and diluted, the slurry concentration is 300g / L, PS=0.367μm, PSD=1.582, stirring is started, and the temperature is raised to 30°C; within 10 minutes, the pH is adjusted to 8.5 with NaAlO2 solution and homogenized for 5 minutes; within 20 minutes, 0.7% NaAlO2 solution and 0.4% Al2(SO4)3 solution (calculated as Al2O3) are added to the slurry at the same time, the pH is 10, and homogenized for 5 minutes; within 20 minutes, Add H2SO4 to the slurry to adjust the pH to 2.5 and homogenize for 10 minutes; add 10% Na2SiO3 solution within 50 minutes and homogenize for 30 minutes; adjust the pH of the slurry to 9 with NaOH, and add 2.2% NaAlO2 solution and 1.3% Al2SO4 solution at the same time, maintain the pH of the slurry at 9, add time 30 minutes, and homogenize for 120 minutes; adjust the pH to 6.5 with H2SO4 within 30 minutes, homogenize for 120 minutes; wash with water, flash evaporation, and steam powder to obtain the product.

[0065] Comparative Example 3

[0066] Foreign standard sample T.

[0067] Examples 1 to 2 and comparative examples 1 to 3 were compared in terms of preparation process, physical and chemical indicators, and application performance. The results are shown in Tables 1 to 2.

[0068] Table 1

[0069]

[0070] From the data, it can be seen that the viscosity of the coating process of the embodiment of the present application is lower than that of the comparative example, the water consumption for washing is small, and the resistivity of the finished product is high (a certain sodium salt is used in the coating process of comparative example 2 and conventional technology, and finally exists in the solution in the form of sodium sulfate or sodium chloride, which needs to be washed away later. Even after washing, some salt may still remain, resulting in a low resistivity, while the barium sulfate in the present application is precipitated in the form of a film layer and does not exist in the solution), less salt, low viscosity in the application system, and is conducive to dispersibility.

[0071] The samples prepared in the embodiment and the comparative example were subjected to latex paint evaluation experiments, and the experimental results are shown in Table 2.

[0072] Table 2

[0073] L a b Covering power Storage stability Example 1 96.32 -0.17 2.01 90.46 good Example 2 96.29 -0.16 2.03 90.31 good Example 3 96.35 -0.15 2.02 90.52 good Example 4 96.21 -0.17 2.01 90.38 good Comparative Example 1 96.16 -0.14 2.09 89.59 good Comparative Example 2 96.61 -0.18 2.12 89.87 Difference Comparative Example 3 96.48 -0.19 2.11 89.72 Difference

[0074] It can be seen from the above table that the invention is significantly better than the comparative example in terms of hiding power and storage stability (dispersibility after being placed for a period of time under specific conditions).

[0075] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A heavy-coated titanium dioxide for coating, characterized in that: It comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from the inside to the outside, a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer; The first aluminum oxide and barium sulfate composite coating layer is formed by adding Ba(AlO2)2 and Al2(SO4)3 to the titanium dioxide-based material slurry and homogenizing them; The second aluminum oxide and barium sulfate composite coating layer is formed by adding Ba(AlO2)2 and Al2(SO4)3 simultaneously and homogenizing them; The total coating amount of the coating layer is not less than 10% of the mass of the titanium dioxide substrate; The coating amount of the loose silicon oxide coating layer is 8-10% of the mass of the titanium dioxide substrate in terms of silicon oxide; The coating amount of the first aluminum oxide and barium sulfate composite coating layer is 2-3.5% of the mass of the titanium dioxide substrate; The coating amount of the second aluminum oxide and barium sulfate composite coating layer is 1.5-3.0% of the mass of the titanium dioxide substrate.

2. The heavy-coated titanium dioxide for coating according to claim 1, characterized in that: The loose silicon oxide coating layer is formed by the following steps: First, the pH of the titanium dioxide-based material slurry is adjusted, and then a soluble alkaline silicon source is added, wherein the soluble alkaline silicon source is added for 30 to 50 minutes, and the loose silicon oxide coating layer is obtained after homogenization for 20 to 40 minutes; wherein the pH is adjusted to a pH of 6.5 to 7.5 after the soluble alkaline silicon source is added; The coating temperature of the loose silicon oxide coating layer is 25-40°C.

3. The heavily coated titanium dioxide for coating according to claim 2, characterized in that: The pH is adjusted to 2-3, and the soluble alkaline silicon source is barium silicate.

4. The method for preparing the heavily coated titanium dioxide for coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: Take titanium dioxide-based material slurry, and coat it with a first aluminum oxide and barium sulfate composite coating layer, a loose silicon oxide coating layer, and a second aluminum oxide and barium sulfate composite coating layer in sequence to obtain the heavily coated titanium dioxide for coating.

5. The method for preparing the heavily coated titanium dioxide for coating according to claim 4, characterized in that: The PS of the titanium dioxide-based material slurry is 0.36-0.38 μm, and PSD is less than 1.

6.

6. The method for preparing the heavily coated titanium dioxide for coating according to claim 4, characterized in that: The preparation method further comprises the following steps: S1. Take titanium dioxide-based material slurry and adjust the temperature to 25~40°C; S2. The pH of the slurry is adjusted to 8-10, and then Ba(AlO2)2 and Al2(SO4)3 are added simultaneously, and the pH of the co-current is maintained at 8.5-9.5, and a first aluminum oxide and barium sulfate composite coating layer is formed after homogenization; the amount of Ba(AlO2)2 is 1.4-2.5% of the mass of the titanium dioxide substrate; the amount of Al2(SO4)3 is 0.6-1.2% of the mass of the titanium dioxide substrate; S3. Adjust the pH of the slurry to 2-3, ensuring that the pH is between 6.5 and 7.5 after adding the soluble alkaline silicon source in step S4; S4. Add a soluble alkaline silicon source for 30 to 50 minutes, and then homogenize for 20 to 40 minutes to form the loose silicon oxide coating layer; the amount of the soluble alkaline silicon source is 8 to 10% of the mass of the titanium dioxide substrate in terms of silicon oxide; S5. Add Ba(AlO2)2 and Al2(SO4)3 at the same time, maintain the co-current pH at 6.5-7.5, and form a second alumina and barium sulfate composite coating layer after homogenization; the amount of Ba(AlO2)2 is 1.0-2.0% of the mass of the titanium dioxide substrate; the amount of Al2(SO4)3 is 0.5-1.0% of the mass of the titanium dioxide substrate.

7. The method for preparing the heavily coated titanium dioxide for coating according to claim 6, characterized in that: The pH adjusting agent in step S2 is Ba(AlO2)2, and the pH adjusting agent in step S3 is sulfuric acid.

Citation Information

Patent Citations

  • Synthesis method of high-dispersion barium sulfate coated with silicon and aluminum on surface

    CN104192888A

  • Titanium dioxide for decorative paper and preparation method

    CN111334092A